Photoperiod and Vernalization Control of Flowering-Related Genes: A Case Study of the Narrow-Leafed Lupin (Lupinus angustifolius L.) - Rychel-Bielska, Sandra; Plewiński, Piotr; Kozak, Bartosz; Galek, Renata; Ksia̧żkiewicz, Michał (Frontiers in Plant Science, 2020)
Narrow-leafed lupin (Lupinus angustifolius L.) is a moderate-yielding legume crop highly appreciated for its high grain protein content and contribution to soil improvement. It is cultivated under photoperiods ranging from 9 to 17 hours, as a spring-sown (in colder locations) or as an autumn-sown crop (in warmer regions). Wild populations require prolonged cold period, called vernalization, to induce flowering. The key achievement of L. angustifolius domestication was a discovery of two natural mutations (named Ku and Jul) conferring vernalization independence. These mutations are overlapping deletion variants in the promoter of LanFTc1, a homolog of the A. thaliana FLOWERING LOCUS T (FT) gene,. Third deletion, named here as Pal, has been recently found in primitive germplasm. In this study, L. angustifolius germplasm differing in domestication status and geographical origin was genotyped for LanFTc1 alleles, and phenotyped for flowering time and vernalization responsiveness. Ku and Jul lines were vernalization-independent and early flowering, wild (ku) lines were vernalization-dependent and late flowering, whereas Pal line conferred intermediate phenotype. Three lines representing Ku, Pal and ku alleles were subjected to gene expression survey under 8-hour and 16-hour photoperiods. FT homologs (LanFTa1, LanFTa2, LanFTc1 and LanFTc2) and some genes selected by recent expression quantitative trait loci mapping were analyzed. Expression profiles of LanFTc1 and LanAGL8 (AGAMOUS-like 8) matched observed differences in flowering time between genotypes, highlighted by high induction after vernalization in ku line. Moreover, these genes revealed altered circadian clock control in Pal line under short days. LanFD (FD) and LanCRLK1 (CALCIUM/CALMODULIN-REGULATED RECEPTOR-LIKE KINASE 1) were negatively responsive to vernalization in Ku and Pal lines but positively responsive or variable in ku, whereas LanUGT85A2 (UDP-GLUCOSYL TRANSFERASE 85A2) was significantly suppressed by vernalization in all lines. Such a pattern suggest opposite regulation of these gene pairs in vernalization pathway. LanCRLK1 and LanUGT85A2 are homologs of A. thaliana genes involved in FLOWERING LOCUS C (FLC) vernalization pathway. Lupins, like many other legumes, do not have any FLC homologs. Therefore, candidate genes surveyed in this study, namely LanFTc1, LanAGL8, LanCRLK1 and LanUGT85A2, may constitute anchors for further elucidation of molecular components contributing to vernalization response in legumes.